1997
DOI: 10.1159/000119381
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Avoidance and Impaired Endurance Capacity in Patients with Panic Disorder

Abstract: Exercise habits and indices of aerobic fitness as measured by spiroergometric testing were examined in 38 patients with panic disorder and/or agoraphobia and 24 untrained healthy controls. Maximal oxygen consumption, maximal power output and the power output at a lactate concentration of 4 mmol/l were significantly reduced in the patient group when compared to untrained controls. Other parameters like physical work capacity at a heart rate of 150/min, maximal lactate concentration, vital capacity, subjective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 7 publications
4
29
1
12
Order By: Relevance
“…[1][2][3] The extent to which their poorer aerobic performances may be related to the actual function of their cardio-respiratory system or affected by psychological variables, such as anxiety levels during fitness testing or catastrophic misinterpretation of physical symptoms has not, however, been satisfactorily clarified; one study showed that high anxiety sensitivity may partly contribute to poor cardiovascular fitness estimation and exercise intolerance in patients with PD. 3 Thus, to evaluate the influence of psychological variables on fitness estimation assessment of patients with PD, we investigated the possible association between their cardiorespiratory response and perceived exertion during submaximal exercise, as well as their state anxiety both before and during exercising, trait anxiety, fear of physical sensations, and fear of autonomic arousal.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The extent to which their poorer aerobic performances may be related to the actual function of their cardio-respiratory system or affected by psychological variables, such as anxiety levels during fitness testing or catastrophic misinterpretation of physical symptoms has not, however, been satisfactorily clarified; one study showed that high anxiety sensitivity may partly contribute to poor cardiovascular fitness estimation and exercise intolerance in patients with PD. 3 Thus, to evaluate the influence of psychological variables on fitness estimation assessment of patients with PD, we investigated the possible association between their cardiorespiratory response and perceived exertion during submaximal exercise, as well as their state anxiety both before and during exercising, trait anxiety, fear of physical sensations, and fear of autonomic arousal.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with panic disorder, the same oral dose of m-CPP led to marked sensations of anxiety, activation, altered self-reality, depression, dysphoria, and subjective functional deficit, and more than half of the patients experienced panic attacks or acute anxiety very similar to panic attacks (Broocks et al 1998b). At the same time, patients with panic disorder are characterized by exercise avoidance and markedly reduced aerobic fitness (Broocks et al 1997;Martinsen et al 1989;Miyakoda et al 1990;Roth 1989;Roth et al 1986;Taylor et al 1987). Abstinence from exercise seems to be a clinically relevant component of the phobic avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…During the 3-minute recovery phase, beginning immediately, speed was decreased and maintained for 1 minute per decrement. Perceived exertion was evaluated by the patient at each stage of the exercise test on a 15-point linear scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as described by Borg. 37 …”
Section: Methodsmentioning
confidence: 99%
“…6 Alternatively, simpler explanations may have been overlooked. Aerobic exercise may be avoided by many PD patients 7 and sedentariness is known to be associated with increased cardiovascular risk. 8 In addition, exercise may induce acute panic attacks (PAs) 9,10 or increase subjective anxiety in patients with PD more than in other people.…”
Section: Introductionmentioning
confidence: 99%